Your Time Zone or Mine? A Study of Globally Time Zone-Shifted Collaboration - Zhao, Chen; Tang, John; Cao, Xiang; Inkpen, Kori (CSCW 2011, 2011)
We conducted interviews with sixteen members of teams that worked across global time zone differences. Despite time zone differences of about eight hours, collaborators still found time to synchronously meet. The interviews identified the diverse strategies teams used to find time windows to interact, which often included times outside of the normal workday and connecting from home to participate. Recent trends in increased work connectivity from home and blurred boundaries between work and home enabled more scheduling flexibility. While email use was understandably prevalent, there was also general interest in video, although obstacles remain for widespread usage. We propose several design implications for supporting this growing population of workers that need to span global time zone differences.